Advances in the activity evaluation and cellular regulation pathways of food-derived antioxidant peptides. (April 2022) - Lv, Renzhi; Dong, Yifei; Bao, Zhijie; Zhang, Simin; Lin, Songyi; Sun, Na
Abstract: Background: Oxidative stress is the main reason for inducing cell apoptosis, tissue damage and pathological changes in the body. Antioxidants can be taken to eliminate radicals and reduce the incidence of hypertension, cardiovascular disease, and hypertension. Food-derived antioxidant peptides are prepared by enzymatic hydrolysis of edible protein. Because of its small molecular weight, high antioxidant activity, and strong safety characteristics, it has gradually become a safe and effective antioxidant. Scope and approach: This article provides a detailed and up-to-date review of food-derived antioxidant peptides from their preparation, activity evaluation, transport and absorption, mechanism of action, and antioxidant-mediated functional activities. In addition, this review emphasizes multiple targeted regulatory pathways of antioxidant peptides to clarify how they exert their mediated functional activity. Key findings: Antioxidant peptides from different sources may have different biological activities and targeting functions due to their natural ingredients and preparation methods. The properties of the polypeptide can be improved by adjusting the parameters of enzymatic hydrolysis. In addition, PEF and Maillard reaction treatment can also enhance the activity of food-derived peptides. The antioxidant mechanism of food-derived peptides can be divided into three types, regulating the production of ROS, regulating enzyme activity, and regulating the antioxidant pathway. Our review especially describes the regulation and molecular mechanisms of Keap1-Nrf2-ARE, NF-κB, MAPK and PI3K/AKT/mTOR pathways. Finally, peptides may act on multiple pathways simultaneously to exert their antioxidant-mediated functional activities. Nowadays, food-derived antioxidant peptides have become a new research direction in functional foods, and have broad prospects. However, how to use food-derived antioxidant peptides that gradually replace synthetic antioxidants requires further research. Highlights: Physical and chemical modifications can improve the activity of peptides. Intestinal transport and absorption of some peptides were elucidated. This article focuses on the multiple mechanisms of antioxidant peptides. The molecular mechanism of peptides targets regulating antioxidant pathways. A peptide can simultaneously exert antioxidant and mediated biological functions.